School resilience through quality management in early childhood education: a case study from Indonesia - Arifiyanti, Nurul; Dwiningrum, Siti Irene Astuti; Syamsudin, Amir; harun, Harun (International Journal of Evaluation and Research in Education (IJERE), 2025)
Poor management of the education system can cause a decrease in school quality. Moreover, the increasing of similar institutions in early childhood education (ECE) in Indonesia gives a school must have good resilience. These institutions must ensure that the educational programs they provide to children are of high quality, thus earning the trust of preschool parents. This article aimed to highlight the importance of paying attention to school management. Therefore, schools that already have good resilience need to be studied to have an impact on schools that are in the stagnant category. The method used was a case study with in-depth interviews. The results indicate that the resilience schools use four strategies to remain resilient. These strategies include having quality human resources, unique school programs, and school promotion. The research results highlight the importance of quality human resource management, superior programs such as foreign language learning and international curricula, and effective promotion in maintaining the resilience of educational institutions amidst competition.